2018
DOI: 10.3390/molecules23112862
|View full text |Cite
|
Sign up to set email alerts
|

Stable Isotope-Labeled Lipidomics to Unravel the Heterogeneous Development Lipotoxicity

Abstract: Non-alcoholic fatty liver disease (NAFLD) as a global health problem has clinical manifestations ranging from simple non-alcoholic fatty liver (NAFL) to non-alcoholic steatohepatitis (NASH), cirrhosis, and cancer. The role of different types of fatty acids in driving the early progression of NAFL to NASH is not understood. Lipid overload causing lipotoxicity and inflammation has been considered as an essential pathogenic factor. To correlate the lipid profiles with cellular lipotoxicity, we utilized palmitic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 48 publications
(54 reference statements)
0
7
0
Order By: Relevance
“…Seven papers of accumulated datasets studied the effects of sugars [ 63 , 64 ], acids [ 65 , 66 ], and other “neutral” compounds [ 67 , 68 , 69 ]. One work was devoted to the impact of gamma-irradiation [ 70 ] on the HepG2 cell line.…”
Section: Resultsmentioning
confidence: 99%
“…Seven papers of accumulated datasets studied the effects of sugars [ 63 , 64 ], acids [ 65 , 66 ], and other “neutral” compounds [ 67 , 68 , 69 ]. One work was devoted to the impact of gamma-irradiation [ 70 ] on the HepG2 cell line.…”
Section: Resultsmentioning
confidence: 99%
“…The present work also demonstrated that Pal administration caused lipid accumulation in HepG2 cells, with a significant elevation of lipid droplets. Besides, several lipidomics studies have noted that Pal can influence the overall lipid metabolism ( Shih et al, 2018 ; Cabezas et al, 2022 ). For example, Pal insult could affect lipid metabolites such as PE, PS, PC, and glycerophosphocholine (GPC) ( Cabezas et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, Pal insult could affect lipid metabolites such as PE, PS, PC, and glycerophosphocholine (GPC) ( Cabezas et al, 2022 ). The stable isotope-labeled lipidomics on Pal-stimulated HepG2 cells revealed that Pal significantly altered the levels of many lipids ( e.g., PL, Cer, GL, et al ), which were involved in biosynthetic pathways of DG, TG, PI, dihydroceramide (dHCer), Cer, SM, PC, PE, LPA, and LPE ( Shih et al, 2018 ). Our lipidomics study also showed Pal-induced a significantly dysregulated lipid profile in HepG2 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Lipotoxicity induced cell death may be another reason. Lipotoxicity is the best studied in liver diseases [99], but it also occurs in cancer cells. For example, saturation or monounsaturation of fatty acids induced apoptotic cell death in liver cancer cells [100].…”
Section: The Potential Interpretations For the Discrepancy In The Role Of Lipid Metabolism Reprograming In Cancermentioning
confidence: 99%